Application of nanofiltration processes to fluoride removal from groundwaters in the Chiang Mai Basin - Yasuhiro Matsui (2018)
The highly concentrated fluoride in groundwater has been observed in the confined aquifers of the alluvial sediments in the Chiang Mai Basin. Nanofiltration process was applied to the control of fluoride exposure to the local residents, who have suffered from serious dental and osteal fluorosis. The membrane plants used polyamide nanofilters, which were found to have different fluoride removal rates depending on pH of feed waters. Although fluoride removal rates were high at neutral to basic pH, calcium carbonate scale on the membrane surface was estimated to be the major problem in membrane fouling. Optimum combination of pretreatment in the membrane plant was evaluated through the investigation on the groundwater quality and the operational conditions.